2017
DOI: 10.1523/jneurosci.3766-16.2017
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Appetitive Associative Strength Modulates Nucleus Accumbens, But Not Orbitofrontal Cortex Neuronal Ensemble Excitability

Abstract: Cues that predict the availability of food rewards influence motivational states and elicit food-seeking behaviors. If a cue no longer predicts food availability, then animals may adapt accordingly by inhibiting food-seeking responses. Sparsely activated sets of neurons, coined "neuronal ensembles," have been shown to encode the strength of reward-cue associations. Although alterations in intrinsic excitability have been shown to underlie many learning and memory processes, little is known about these properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(44 citation statements)
references
References 60 publications
3
41
0
Order By: Relevance
“…One possible scenario is that different neuronal ensembles intermingle within PLC that encode separate learned associations or memories (Warren et al, 2016). This seems likely given the diverse role of PLC in attentional allocation, contextual encoding, and rewarding and aversive learning (Watanabe, 1996;Schall et al, 2002;Fujii and Graybiel, 2003;Euston et al, 2012;Sharpe and Killcross, 2014;Pinto and Dan, 2015). In support of this idea, recently, we demonstrated a critical role of infralimbic cortex (ILC) neuronal ensembles in both operant learning and extinction of the operant response (Warren et al, 2016).…”
Section: Intrinsic Excitability Alterations Within Fos-expressing Neumentioning
confidence: 99%
See 1 more Smart Citation
“…One possible scenario is that different neuronal ensembles intermingle within PLC that encode separate learned associations or memories (Warren et al, 2016). This seems likely given the diverse role of PLC in attentional allocation, contextual encoding, and rewarding and aversive learning (Watanabe, 1996;Schall et al, 2002;Fujii and Graybiel, 2003;Euston et al, 2012;Sharpe and Killcross, 2014;Pinto and Dan, 2015). In support of this idea, recently, we demonstrated a critical role of infralimbic cortex (ILC) neuronal ensembles in both operant learning and extinction of the operant response (Warren et al, 2016).…”
Section: Intrinsic Excitability Alterations Within Fos-expressing Neumentioning
confidence: 99%
“…The PLC is a functionally diverse structure within the prefrontal cortex that plays a critical role in goal-directed behavior and learning (Baldwin et al, 2002;Corbit and Balleine, 2003;Fujii and Graybiel, 2003;Euston et al, 2012) and is active during the presentation of reward or reward-predictive cues (Watanabe, 1996;Matsumoto et al, 2007;Moorman and Aston-Jones, 2015;Pinto and Dan, 2015). We then used an ex vivo brain slice preparation in FosGFP-transgenic rats (Cifani et al, 2012) to identify Fos/GFP-expressing neurons that were strongly activated during operant food self-administration and assessed intrinsic excitability in FosGFP ϩ and FosGFP Ϫ neurons.…”
Section: Introductionmentioning
confidence: 99%
“…Following learning in vivo , enhanced excitability distinguishes ensembles of SPNs engaged to retain recently learned associations (Ziminski et al . ), and dorsomedial SPNs show transiently enhanced intrinsic excitability proximal to new learning (Hawes et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…While it is clear that the SK channel is an important modulator of excitability and a frequent target in studies of associative learning, its role in activity-dependent ensembles and addiction is yet to be explored. Neuronal excitability increases after learning Ziminski et al 2017Ziminski et al , 2018. (Bottom) Example of synaptic changes in a Fos neuron before and shortly after drug-based learning experience.…”
Section: The Role Of the Sk Channel In Fos-expressing Ensembles And Nmentioning
confidence: 99%
“…Synaptic alterations are likely induced during subsequent training sessions so that the relevant cue-specific inputs can more reliably and efficiently activate the most strongly activated ensemble neurons Yiu et al 2014;Whitaker et al 2016). This coupled with shifts in the intrinsic membrane properties of cue-selected ensemble neurons across training may lead to the selection of particular neurons as ensemble neurons Ziminski et al 2017Ziminski et al , 2018. However, a different line of studies found that constitutive overexpression of the transcription factor CREB "before" learning or cue experience led to preferential recruitment of lateral amygdala neurons into an ensemble encoding cue-cocaine associations, or a "cocaine engram" .…”
Section: Functional Engram Formation During Learningmentioning
confidence: 99%